Observational cross-sectional study on Symptoms Associated to Moisture DAmage at Workplace: the SAMDAW study protocol. Issue 6 (25th June 2019) - Nynäs, Pia; Vilpas, Sarkku; Kankare, Elina; Karjalainen, Jussi; Lehtimäki, Lauri; Numminen, Jura; Tikkakoski, Antti; Kleemola, Leenamaija; Uitti, Jukka
Abstract : Introduction: Moisture damage (MD) exposure at work has been shown to increase the risk of new onset asthma and exacerbation of asthma. However, most of the studies in this field have been questionnaire studies. A small proportion of MD-exposed workers are diagnosed with asthma. Many patients with MD exposure at work referred to secondary healthcare report intermittent hoarseness, loss of voice or difficulty to inhale, referring to functional or organic problems of the larynx. For accurate treatment, proper differential diagnostics is paramount. We present an ongoing observational study in which we describe the prevalence of respiratory, voice and other symptoms related to MD at work in patients referred to secondary healthcare. Case-control setting will be used to evaluate the frequencies of the background factors, bronchial hyperreactivity and laryngeal findings. Methods and analysis: The study sample consists of patients with workplace MD exposure and associated respiratory tract and/or voice symptoms referred to Tampere University Hospital. The clinical tests conducted to the study patients included comprehensive lung function tests, laboratory and skin prick tests, imaging and clinical evaluation by specialists of respiratory medicine, oto-rhino-laryngology and phoniatrics. The exposure assessment was performed by an occupational physician. The study patients filled out a questionnaire on previous illnesses and other background factors, which for comparison was also sent to 1500 Finnish-speaking people in the same hospital district randomly selected by the Finnish Population Information System. To explore how common laryngeal disorders and voice symptoms are in general, a part of the tests will be conducted to 50 asymptomatic volunteers. Ethics and dissemination: The regional ethics committee of Tampere University Hospital approved the study. All study subjects gave their written informed consent, which is required also from the controls. The results will be communicated locally and internationally as conference papers and journal articles.